ANALISIS NUMERALIA BAHASA MOI RAGAM KELIN DI KAMPUNG KLAYILI DISTRIK KLAYILI KABUPATEN SORONG - agustinus gideon gifelem; Wifas Asmuruf; Yerry Faluk (LPPM Politeknik Saint Paul Sorong, 2021)
This paper aims to analyze number of words Moi language Variety kelin in city and sorong regency. Data analysis has used a qualitative approach. Based on the analysis conducted, it has found varieties number of words in Moi language Variety kelin. Based on raw data obtained the data is classified based on the theories of Alwin et al. so it can be stipulated clearly that in Moi language variety kelin there are several words of number among other: words of number (principal number of words, words of number, and the words of indefinite number) and words of number (words of phrase number)